Analysis of Screen Time for Online Gaming and Screening Children's Visual Acuity in the Pandemic Era - Minarni Wartiningsih; Hanna Tabita Hasianna Silitonga; Victor Setiawan Tandean; Gusto Benyamin Messakh; Aldy Dion; Firda Aulia Wiraputri (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2023)
One of the causes of pediatric eye vision problems in the pandemic era is the increased use of digital screen devices to play online games. This is due to an increase in accommodation and convergence in the eyes when doing activities through digital screen devices at close range. The purpose of this study was to determine the relationship between screen time duration and visual acuity in children aged 9-12 years in the Kalongan and Sidokerto Malang areas during the Pandemic era. This research is a descriptive observational quantitative research with a cross-sectional research design. The research sample was 62 children with a saturated sampling method or a number of population members. The research was conducted in the community of school-age children in the Kalongan and Sidokerto Malang areas. The data used in this study were primary data giving questionnaires to children through parents and checking children's visual acuity. The analysis method used in this research is a univariate and bivariate analysis using the chi-square test.  Based on the results of the study, the majority of respondents play online games. Some respondents experienced decreased visual acuity. There is a correlation between the duration of playing online games and the visual acuity of the right and left eyes. Children who play online games for longer periods of time (more than 2 hours) are more likely to experience decreased visual acuity than children who play online games for less than 2 hours or do not play online games.